A Contrast of Parallelisms and Confrontations: The Other Wes Moore Experiences on a PWI Campus flier - Kansas State University, K-State First (Kansas State University. K-State First., 2015)
This flier advertised the panel discussion, "A Contrast of Parallelisms and Confrontations: The Other Wes Moore Experiences on a PWI Campus", presented by Dr. Be Stoney from Kansas State University's Department of Education. A panel of students from the Phi Beta Sigma fraternity discussed their parallelisms and confrontations based on "The Other Wes Moore" and their experiences at a Predominately White Institutions (PWI).
Keywords: The Other Wes Moore; Events; Common reading program; Engagement; Faculty lecture; Race; Promotional materials